Applying New Innovative Market Research Methods in the Innovation Process of New Products - Gál, Tímea; Soós, Mihály; Szakály, Zoltán (International Journal of Engineering and Management Sciences, 2017)
The innovation environment has changed a lot in the recent years, companies and their enterprises concentrating on product- and process innovation have undergone a lot of changes. According to GUPTA et al. (1986) product innovation is a multidisciplinary process. Although, all functional interfaces are important in the product development process, the research and development – marketing interface is one of the most difficult one. In the last two decades the incredibly fast penetration of the internet has more and more effects on the consumer attitudes. It encourages market researchers to apply such methods by which they could get as close as to the consumers to know their attitudes without taking them out of their natural habitat. In this study our aim is to concentrate on the first phase of the product innovation, which is the exploration of insights and attitudes. In this phase we can use the classical, conventional market research techniques if we want to get primary data, such as focus group interviews, questionnaires, in-depth interviews, but there are new methods as well. One of such novel methods is netnography. The biggest advantage of this research method is that the researcher can observe the consumer groups’ state of mind and decision-making mechanisms through publicly available communication sources in their natural environment. In this study it will be analysed how the directions of netnographic researches have changed by the dynamic changes of the internet. Besides, online participants’ attitudes towards healthconscious nutrition are analysed in practice. As a result of this study, special groups could be identified, which can provide a new perspective for the companies operating in this field beside the classical segmentation techniques. These groups can be the ones which draw up latent market requirements, and thus, helping the companies’ innovation processes.